2022
DOI: 10.1088/1748-3190/ac98e5
|View full text |Cite
|
Sign up to set email alerts
|

Capturing wake capture: a 2D numerical investigation into wing–wake interaction aerodynamics

Abstract: A wing generating lift leaves behind a region of disturbed air in the form of a wake. For a hovering insect, the wings must return through the wake produced by the previous half-stroke and this can have significant effects on the aerodynamic performance. This paper numerically investigates 2D wings interacting with their own wake at Reynolds numbers of 102 and 103, enabling an improved understanding of the underlying physics of the ‘wake capture’ aerodynamic mechanism of insect flight. We adopt a simple kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It occurs due to the flow induced by two counter-rotating forefoil wake vortices during pronation, represented by an arrow in figure 5(a). Such type of flow phenomena, where the foil interacts with its own wake vortices generated during previous stroke, is known as 'wake capture' or 'wing-wake interaction' [33][34][35]. This causes an early shedding of the forefoil TEV (figure 5 Figure 6 shows that thrust generation (negative C H ) mostly occurs during upstroke, whereas downstroke plays a smaller role.…”
Section: Resultsmentioning
confidence: 99%
“…It occurs due to the flow induced by two counter-rotating forefoil wake vortices during pronation, represented by an arrow in figure 5(a). Such type of flow phenomena, where the foil interacts with its own wake vortices generated during previous stroke, is known as 'wake capture' or 'wing-wake interaction' [33][34][35]. This causes an early shedding of the forefoil TEV (figure 5 Figure 6 shows that thrust generation (negative C H ) mostly occurs during upstroke, whereas downstroke plays a smaller role.…”
Section: Resultsmentioning
confidence: 99%
“…Reynolds number is known to affect the shape of vortex structures in a profound way, which would in turn affect the amplitude of the wake capture force peaks. The recent study of Li & Nabawy [36] has shown that the wake capture effect becomes stronger as the Reynolds number increases over ). Finally, the use of different switching gains to fit different experimental results should not be seen as a major concern as it was shown that the way the model input parameters affect the wake capture results is independent from the value of the switching gain.…”
Section: Limitations Of the Current Modelmentioning
confidence: 98%
“…I believe it is useful to stop here and consider the aspect ratio effect on wake capture lift, in light of some of the recent findings within the flapping wing aerodynamics field [35,36]. In particular, a recent experimental campaign from Addo-Akoto et al [35] considered the wing aspect ratio influence on wake capture aerodynamics.…”
Section: Sensitivity To Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the LEV of a 2-D aerofoil always sheds in a translating motion. This discrepancy in the spatial-temporal status of the LEV can affect the wing–wake interaction because the LEV attachment status has been proven to determine the specific contribution of inter-vortex jet and single-vortex suction mechanisms (Li & Nabawy 2022). Specifically, how the unsteady evolution of an outboard LEV affects the wing–wake interaction is still unclear.…”
Section: Introductionmentioning
confidence: 99%